High yields of riparian buffer strips planted with Salix miyabena 'SX64' along field crops in Québec, Canada. (October 2017) - Hénault-Ethier, Louise; Gomes, Marcelo Pedrosa; Lucotte, Marc; Smedbol, Élise; Maccario, Sophie; Lepage, Laurent; Juneau, Philippe; Labrecque, Michel
Abstract: In the province of Québec, Canada, a policy for protecting shores recommends the presence of 3 m wide riparian buffer strips (RBS) along field crops to minimize agro-chemical leaching to surface waters. Fast-growing woody crops like Salix miyabeana 'SX64' could generate revenues from energy dedicated biomass production within the RBS land area withdrawn from grain production. To determine the potential biomass productivity, experimental RBS were established on two sites — Saint-Roch-de-l'Achigan (SR) and Boisbriand (BB) — with three treatments set up in triplicata composed of mixed herbaceous vegetation (CX), low (3X: 3 rows) and high (5X: 5 rows) density plantations of willows. Growth (stem number, diameter and height) was measured annually from 2011 to 2014; and yield (Mg dw·ha −1 ) was measured in 2014. Growth and yield significantly differ between sites (SR < BB). In the 3 m wide strips, 23-24 Mg dw stems·ha −1 ·year −1 yield in compacted sandy loam soil at SR resembles typical field productions but the 56–89 Mg dw stems·ha −1 ·year −1 in a humisol at BB is larger compared to field plantations. In the light of the present research, we conclude that considerable biomass productivity may be produced in RBS. This result should be considered along with harvesting, transformation or market opportunities to help farmers assess the viability of this practice on their farm. Graphical abstract: Highlights: Salix miyabeana SX64 grows well in riparian buffer strips. Narrow riparian buffer strips along agricultural fields yield high biomass. 23–24 t dw stems·ha −1 ·year −1 in compacted sandy loam resembles field plantations. 56–89 t dw stems·ha −1 ·year −1 in a humisol is a record in the Salix literature.